KEPADATAN DAN POLA PENYEBARAN PASAK BUMI (Eurycoma longifolia Jack) DI ZONA ALAMAN KUYANG, HUTAN LARANGAN ADAT KENEGARIAN RUMBIO - ZULFAHMI ZULFAHMI; NELAWATI NELAWATI; ROSMAINA ROSMAINA (Jurnal Agroteknologi, 2015)
The objective of this research was to know the density and distribution pattern of E. longifolia in the Alaman Kuyang zone of the forest reserve of Kenegerian Rumbio. The research used purposive sampling method. The observation plot is made in square plot  which plot size was 20 x50 m.  Results of this study showed that density  of E. longifolia in Alaman Kuyang zone of forest reserve of Kenegarian Rumbio was 130 individual ha-1, which seedling phase is more dominance than  sapling and pole phases. The density of E.longifolia was low due to increasing the harvesting of this species from forest reserve of Kenegarian Rumbio, and addition poor of mother trees in area study. Distribution pattern of E. longifolia were clumped with Morisita Index value > 1, this could be explained since seed of E. longifolia dispersed and grew not far from mother trees.